The Effectiveness of Formative Assessment in Improving Students’ Writing Skill - trismayanti, ni komang (Jurnal Ilmiah Pendidikan Profesi Guru, 2021)
Assessment is one of the most important parts in teaching and learning process. There are many types of assessment and formative assessment is one of them. The use of formative assessment is beneficial in improving students’ performance, especially in writing skill. This article aims to review the effectiveness of formative assessment in improving students’ writing skill as well as to analyze teachers and students’ perceptions toward the use of formative assessment in writing skill. In collecting the data, this article used library research as a method. The data were collected from the previous study in the form of journals, articles, and thesis. The result of the research showed that the implementation of formative assessment is effective and beneficial in improving students’ writing skill. Moreover, both teachers and students have a positive attitude toward the use of formative assessment as a media for writing improvement.